On the Hysteretic Behavior of Fully Connected and Beam-Connected Flat-Corrugated Steel Shear Walls with Different Corrugation Angles and Orientations - Zhenhua Guan; Linlin Zhang (Electronic Journal of Structural Engineering, 2025)
Steel Shear Walls (SSWs) have been utilized for years for their significant benefits. In early applications, this system was used without stiffeners, which were subsequently developed and enhanced in multiple ways. A new concept of SSWs called Flat-Corrugated Walls (FCWs) has been introduced recently. This research presents a two-layer SSW composed of smooth and Corrugated Plates (CPs), in which CPs are used in three directions: horizontal, vertical, and diagonal. Moreover, CPs featuring wave angles of 30, 45, and 60 degrees were utilized. Infill Flat-Corrugated Plates (FCPs) were considered fully connected and connected with beams only. In addition, fully connected and beam-connected single-corrugated SSWs (SCSSWs) were studied for comparison in this paper. This research displayed that the resistance of Fully Connected Flat-Corrugated Walls (FC-FCWs) is higher than that of the corresponding Single-Corrugated Wall (SCW), between 0.4 and 15.6%. In the cases linked to the beam, the resistance of FCWs is at least 0.9% and at most 29.2% higher than the corresponding SCWs. The orientation of the CP in FC-FCWs has little effect on the Hysteresis Curve (HC) and structural parameters, providing a stable and reliable performance. While the HC of single-CSSWs is not symmetrical, FCWs have a stable HC, reassuring the audience about the reliability of this system. Increasing the wave angle of the plate has resulted in a greater bearing capacity for flat-CSSWs (FCSSWs). Also, FCSSWs connected to horizontal beams have the lowest resistance compared to other examples.